Ultrasensitive artificial synapse based on conjugated polyelectrolyte. (June 2018) - Xu, Wentao; Nguyen, Thanh Luan; Kim, Young-Tae; Wolf, Christoph; Pfattner, Raphael; Lopez, Jeffrey; Chae, Byeong-Gyu; Kim, Sung-Il; Lee, Moo Yeol; Shin, Eul-Yong; Noh, Yong-Young; Oh, Joon Hak; et al.
Abstract: Emulating essential synaptic working principles using a single electronic device has been an important research field in recent years. However, achieving sensitivity and energy consumption comparable to biological synapses in these electronic devices is still a difficult challenge. Here, we report the fabrication of conjugated polyelectrolyte (CPE)-based artificial synapse, which emulates important synaptic functions such as paired-pulse facilitation (PPF), spike-timing dependent plasticity (STDP) and spiking rate dependent plasticity (SRDP). The device exhibits superior sensitivity to external stimuli andlow-energy consumption. Ultrahigh sensitivity and low-energy consumption are key requirements for building up brain-inspired artificial systems and efficient electronic-biological interface. The excellent synaptic performance originated from (i) a hybrid working mechanism that ensured the realization of both short-term and long-term plasticity in the same device, and (ii) the mobile-ion rich CPE thin film that mediate migration of abundant ions analogous to a synaptic cleft. Development of this type of artificial synapse is both scientifically and technologically important for construction of ultrasensitive highly-energy efficient and soft neuromorphic electronics. Graphical abstract: An artificial synapse is fabricated to emulate biological functions with high sensitivity and low-energy consumption fx1 Highlights: Conjugated polyelectrolyte (CPE)-based artificial synapse was fabricated. Important working principles of a biological synapse are emulated. The artificial synapse potentially exhibited ultrahigh sensitivity and low energy consumption.